Effects of an Eight-Month Exercise Intervention Programme on Physical Activity and Decrease of Anxiety in Elementary School Children - Irina Klizienė; Laura Kimantienė; Ginas Čižauskas; Giedrė Marcinkevičiūtė; Viktorija Treigytė (Lithuanian Sports University, 2018)
Background. The World Health Organization recommends children to participate in sufcient PA by engaging in moderate-to-vigorous physical activity for at least 60 min daily per week. Schools are important settings for the promotion of children's physical activity. Through commuting, breaks, and physical education lessons they provide regular opportunities for children to be active. Methods. The experimental group included 36 girls and 34 boys aged 6-7 years old. Their mean weight and height were 24.3 ± 0.9 kg and 1.25 ± 0.11 m for the girls, and 29.3 ± 0.6 kg and 1.33 ± 0.09 m for the boys. The control group included 35 girls and 33 boys aged 6-7 years old, attending the same school. Their mean weight and height were 22.3 ± 0.7 kg and 1.24 ± 0.1 m for the girls, and 28.4 ± 0.7 kg and 1.36 ± 0.07 m for the boys.The methodology of innovative physical education classes was based on the DIDSFA model (dynamic exercise, intense motor skill repetition, diﬀerentiation, physical activity distribution in the classroom). The evaluation of physical activity. Children's Physical Activity Questionnaire (Corder et al., 2009) was used. It was also based on the Children's Leisure Activities Study Survey (CLASS) questionnaire. The measurement of anxiety - the methodology of Reynolds and Richmond (1994). Results. The post-test of the experimental group boys (1320.24 MET, min/week) was to analyse average physical activity in comparison with the girls of the experimental group (840.60 MET, min/week). Statistically significant diﬀerence was found during the analysis of average MET per boy (1390.45 MET, min/week) in comparison with the girls (880.27 MET, min/week, p < .05). The results of the somatic anxiety in EG (5.54 ± 1.18 points) before theexperiment and after it showed that after the intervention programme somatic anxiety in EG was 5.08 ± 1.09 points.This demonstrates lower levels of depression, seclusion, somatic complaints, aggression and delinquent behavior (F = 4.895, p < .05, P = 0.550). Conclusion. It was established that properly construed and purposefully applied complex of the eight-month exercise intervention programme for elementary school children led to statistically signifcant changes in the dependent variables: increased physical activity and decreased anxiety for the experimental group. Keywords: physical activity, anxiety, innovative physical education classes, primary education.